Implementation of the Independent Learning Curriculum in Inclusive Schools - Shela Andri Mauliddina; Dede Margo Irianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This research post report aims to recognize and analyze the Implementation of the Free Learning Curriculum in Inclusive Schools. This research uses qualitative procedures using a descriptive approach. This method is done by analyzing data or materials obtained from various references such as books, journals, and/or articles. Based on the results of the analysis, it can be concluded that the Independent Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. Inclusion schools are schools that also provide education for children with special needs (ABK). In the end, in the implementation of the independent curriculum, learning in inclusive schools aims at various models and methods.